SOSIALISASI DAN DEMONSTRASI KEGIATAN PENDIDIKAN KREATIF DI BIDANG PERTANIAN DESA BANDAR SAKTI KECAMATAN TERUSAN NUNYAI KABUPATEN LAMPUNG TENGAH - Anggoro, Dicky; putri, dynda sinar; dhika, eduar; fransiska, nurike; samini, samini; Nurdin, Nurdin; Suroto, Suroto (Jurnal Pengabdian Sosial Indonesia, 2024)
KKN is a form of community service activity by students with a cross-scientific and sectoral approach at a certain time and area. The implementation of KKN activities lasts for 40 days starting from 1 February - 12 March 2021. The 2021 independent village KKN held in Bandar Sakti village, Terusan Niliki sub-district, Central Lampung district carries out socialization and training activities for creative education activities aimed at the community, especially teenagers and youth. Children can increase their creativity during the pandemic so that they are more active and productive, where they do not get maximum creativity learning. The results showed that there was a positive response from village officials and high active community participation, including following socialization activities and training in creative education activities with two activities, namely the socialization of verticulture and kokedama making. Verticulture is a cultivation technique in a narrow space / land by utilizing a vertical plane as a multi-level planting place. The purpose of verticulture is so that teenagers become more aware of plant cultivation, use of narrow yards and increase creativity in agriculture. Kokedama is an activity of planting plants (succulents) in a ball of soil which is added with clay as an outer layer so that it does not break easily, then wrapped with wool to make it look more attractive and can be hung as decoration. This activity is aimed at building the enthusiasm for learning with interesting learning to increase creativity, adding insight into useful activities, namely playing while learning so that you are not bored and tired of learning in the pandemic era and improving children's soft skills from an early age to be more active and productive in learning in the future. pandemic.Key words: KKN, verticulture, kokedama